A Novel Strategy for the Treatment of Allergic Rhinitis: Regulating Treg/Th17 and Th1/Th2 Balance In Vivo by Vitamin D. (31st July 2022) - Li, Baowei; Zhang, Xiaoli; Sun, Zhezhe; Xu, Bingxin; Wu, Jihua; Liu, Hongdan; Han, Haolun; Wang, Lei; Wu, Wei
Abstract : Objective. This prospective study is aimed at observing the number of nasal itching and sneezing in rats from the macroscopic level and examine the pathological changes of nasal mucosa, Th1 and Th2-related cytokines, and Treg/Th17 by vitamin D3 administration from the microscopic level, in order to explore the role of vitamin D in allergic rhinitis and to provide theoretical guidance for prevention and treatment. Results. There were significant differences in nasal itching and sneezing between the administration groups and the positive groups. Meanwhile, the level of Th1 and Treg in the administration groups increased, while the level of Th2 and Th17 decreased, indicating that the balance of Th1/Th2 was corrected. Our study revealed that vitamin D3 has preventive and therapeutic effects on allergic rhinitis, which provides theoretical guidance for practical application.